Deformation-based performance index of corroded reinforced concrete beams. (February 2021) - Liu, Xiaojuan; Jiang, Huanjun; Ye, Yong; Guo, Zixiong
Abstract: In order to implement the life-cycle oriented performance-based seismic design of reinforced concrete (RC) structures, quantification of seismic performance indexes for corroded RC members is necessary. Firstly, the material strain-based criteria to classify damage limit states for RC members were proposed. Numerical analysis was conducted with the aid of the software ABAQUS to investigate the deformation behaviour of RC beams. Corrosion ratio of steel reinforcement, shear span ratio and longitudinal reinforcement ratio were considered as the main analytical parameters. It is found that for RC beams with corrosion ratio not exceeding 7.5%, the corrosion ratio of steel reinforcement has little effect on the deformation behaviour of RC beams. For RC beams with corrosion ratio lager than 7.5%, the deformation capacity is significantly affected by the reinforcement corrosion ratio. Based on numerical simulation results, expressions for estimating deformations of corroded RC beams at yield and ultimate limit states were derived, respectively. The deformation limits corresponding to the individual damage limit state of corroded RC beams were proposed. The research results can be utilized for life-cycle oriented seismic performance evaluation and design of RC structures. Highlights: The deformation behaviour of corroded RC beams was investigated. Effects of corrosion ratio, reinforcement ratio and shear span ratio on the deformation capacity of RC beams were evaluated. Expressions for deformations of corroded RC beams at both yield and ultimate states were derived. Deformation limits corresponding to the individual damage limit state of RC beams were proposed.